Synthesis and Characterization of New Extractants for Cu(II) - Zhang, Xing; Hui, Jianbin (Asian Journal of Chemistry, 2013)
New extractants for Cu2+ ions in raw ore powders or waste water (fluid) were successfully synthesized recently in good yields. Their structures and purity were confirmed by 1H NMR and IR.